The Effect of Working Hours System on Employee Productivity At PT. Manakarra Unggul Lestari - Kordiana Sambara; Maria Yessica Halik; Reza Aprianti (Journal of Entrepreneur, Business and Management, 2023)
This study aims to determine the effect of working hours system on employee productivity at PT.Manakarra Unggul Lestari. This type of research that is used is the method of correlation analysis and determination. The sample used in this research is 52 respondents. The variables used are the independent variables, namely the working hours system (X) and the dependent variable employee productivity (Y). The results of the study for work culture on employee performance by means of the t test obtained the value of t = 5.433, which means t count t table (5.433 1.67155). Then the hypothesis states that work culture partially affects employee performance. This can be seen from r = 0.61, which means that the relationship between work culture (X) and employee productivity (Y) is 37%, meaning that there is an adequate relationship, which means that H_0 is rejected and H_a is accepted, so it can be concluded that the working hours system has a significant effect on employee productivity at PT.Manakarra Unggul Lestari. Keywords: Working hours,  System, Employee,  Productivity, PT.Manakarra Unggul Lestari